Substantive and procedural considerations for the adequate imputation of infractions to the Civil Service Code of Ethics from the perspective of the administrative jurisprudence of the Civil Service Tribunal - Morales Morante, Carlos Guillermo (2022)
The aim of this study is to analyze the substantive and procedural aspects related to the exercise of the sanctioning power of the Nation-employer that regulate disciplinary administrative procedures (DAP) in the public legal regime. The proposed theoretical mark begins with the analysis of the relationships between ethics and law, within the framework of the proper exercise of public service, whose normative vertex is the Ethics Code of the Public Service, which constitutes a transversal legal system that is applied in the public administration. Based on this, an overview is to be given of the structure and configuration of the legal regime of offenses and sanctions contained in the aforementioned Code, which classifies as a disciplinary offense the infringement of the principles, duties and prohibitions regulated in its normative system, that define its substantive content, which forces rules to be set for its adequate subsumption within the legal types regulated in the Code, as well as its framing in the rules of the DAP, in compliance with the principles of the sanctioning power of the state. In this sense, this article addresses the substantive issues related to the parameters of legality and typicity that the administrative system enshrines through the Unified Text of the General Administrative Procedure Law, to be considered in the imputation of the offenses contained in the Code, which require their positive concretion based on the application of the rules of the disciplinary regime of the Civil Service Law.